The Concept of Affection and Effect in the Poetry of Al-Qadi Omar Ibrahim - Mohamed, Mohamed Khamis (Arab Journal for Sciences and Research Publishing, 2015)
The Concept of Affection and Effect exist in all aspects of human life. Indeed, any environment surrounding the poet is one of those effects that have a prominent role in the formation of his literary work. Similarly, the Nigerian poet environment does not differ from other environments in West African region in terms of religion and culture. The poet Alkali Umar Ibrahim is one of the Nigerian poets who have been affected greatly and influenced by Western culture, you hardly read his poems until you see some of the features of Western civilization, Indeed, therefore, he is one of the pioneers of the poetic renewal in West African poetry, since he defeated others in dealing with modern poetic inventions apart from technological, political and economic aspects that he had treated. As such, he is influenced by the religion of Islam which is the major religion in the northern part of the country. Therefore, the aim of the paper is to state some of the features of this phenomenon which has worked in the poet, in the sense that it is one of the powerful influences on his approach to poetry and genius. The article began with introduction and brief biography of the poet, and then talked about the issue of affection and effect that had shaped his poetic experience, and then marked the conclusion, margins and references
Keywords: affected; the influence; the judge; Judge Omar Ibrahim; Poetry